2008
DOI: 10.1016/j.ntt.2007.12.006
|View full text |Cite
|
Sign up to set email alerts
|

The effects of prenatal cocaine use on infant development

Abstract: This study examined the effect of prenatal cocaine use on infant physical, cognitive, and motor development, and temperamental characteristics, controlling for other factors that affect infant development. Women were, on average, 26.8 years old, had 12 years of education, and 46% were African American. During the first trimester, 18% were frequent users of cocaine (≥ 1 line/day). The infants were, on average, 14.6 months old at this follow-up phase. Women who used cocaine during pregnancy rated their infants a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
56
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 84 publications
13
56
1
2
Order By: Relevance
“…We have found persistent associations between PCE and child temperament and behavior problems at 1, 3, 7, and 10 years of age (Richardson et al, 2008(Richardson et al, , 2009, which is consistent with reviews suggesting that the behavior domain is most likely to be affected (Ackerman et al, 2010;Behnke et al, 2013;Buckingham-Howes et al, 2013). Others have also reported that PCE is associated with child or adolescent behavior problems, particularly externalizing behaviors such as aggression and delinquency (Bada et al, , 2012Bennett et al, 2007Bennett et al, , 2013DelaneyBlack et al, 2000;Fisher et al, 2011;McLaughlin et al, 2011;Minnes et al, 2010;Nordstrom Bailey et al, 2005;Sood et al, 2005;Whitaker et al, 2011).…”
Section: Introductionsupporting
confidence: 86%
See 3 more Smart Citations
“…We have found persistent associations between PCE and child temperament and behavior problems at 1, 3, 7, and 10 years of age (Richardson et al, 2008(Richardson et al, , 2009, which is consistent with reviews suggesting that the behavior domain is most likely to be affected (Ackerman et al, 2010;Behnke et al, 2013;Buckingham-Howes et al, 2013). Others have also reported that PCE is associated with child or adolescent behavior problems, particularly externalizing behaviors such as aggression and delinquency (Bada et al, , 2012Bennett et al, 2007Bennett et al, , 2013DelaneyBlack et al, 2000;Fisher et al, 2011;McLaughlin et al, 2011;Minnes et al, 2010;Nordstrom Bailey et al, 2005;Sood et al, 2005;Whitaker et al, 2011).…”
Section: Introductionsupporting
confidence: 86%
“…We found significant associations between PCE and growth deficits at follow-ups through 10 years of age (Richardson et al, 1999(Richardson et al, , 2008(Richardson et al, , 2009. Some other studies have also reported that PCE has a detrimental effect on childhood growth (Covington et al, 2002;Minnes et al, 2006;Rivkin et al, 2008;Shankaran et al, 2011).…”
Section: Introductionsupporting
confidence: 68%
See 2 more Smart Citations
“…Both of these drugs have been implicated in mental disorders for the developing child, like mental retardation in the case of alcohol abuse 11 . Thus, although the effects of prenatal cocaine exposure remains unclear 12,13 , since its use is frequently associated to alcohol and tobacco, it puts the baby at risk. Interestingly, some subjects tried to decrease crack-cocaine use during pregnancy, highlighting this period as a time of greater receptivity to therapeutic intervention 14 .…”
Section: Discussionmentioning
confidence: 99%